World Century Compendium to TCM : Introduction to Acupuncture and Moxibustion. - Zhang, Ren (World Century compendium to TCM., 2013)
Acupuncture and moxibustion are one of the most important contributions our ancestors have made to humankind. In the narrow sense, acupuncture and moxibustion refer to medical therapy, whilst broadly, they are an integral science consisting of four subdisciplines: the subject of meridians and acupoints, the subject of acupuncture and moxibustion techniques, the subject of acupuncture and moxibustion therapy, and the subject of experimental acupuncture and moxibustion.